ATTITUDES OF STUDENTS AT FKIP UNIVERSITAS RIAU TOWARD COMPUTER-ASSISTED LANGUAGE LEARNING (CALL) - Masyhur Masyhur (Proceedings of ISELT FBS Universitas Negeri Padang, 2013)
This paper identified attitudes toward CALL of students studying English as a foreign language (EFL) at FKIP Universitas Riau. Seventy students who were enrolled in the orientation year of an English program were chosen to participate in this study by expressing their attitudes toward CALL. Standardized and local instruments were used along with interviews and observation techniques to collect data. The results of the study revealed that students had positive attitudes toward CALL. Looking at the daily hours students spend using a computer, a slight correlation was found between this variable and the students’ attitudes toward CALL. Other variables, such as students’ background knowledge of English, ownership of a computer, and their computer knowledge, were found to be irrelevant to their attitudes toward CALL. These results were in line with previous research conducted by Al-Shammari (2007), Alrumaih (2004), and Almekhlafi (2006). The results reinforced conclusions about CALL revealed by researchers, such as Chen (2003), Chikamatsu (2003), Egbert (2005) and Levy (2005), who found that it helps students learn better and more independently, and gives them the ability to have more control of their learning and to have more opportunities to practice English.